Queer Maghrebi French : language, temporalities, transfiliations - Provencher, Denis M. (Contemporary French and francophone cultures, 2017)
This book investigates the lives and stories of queer Maghrebi and Maghrebi French men who moved to or grew up in contemporary France. It combines original French language data from my ethnographic fieldwork in France with a wide array of recent narratives and cultural productions including performance art and photography, films, novels, autobiographies, published letters, and other first-person essays to investigate how these queer men living in France and the diaspora stake claims to time and space, construct kinship, and imagine their own future. By closely examining empirical evidence from the lived experiences of these queer Maghrebi French-speakers, this book presents a variety of paths available to these men who articulate and pioneer their own sexual difference within their families of origin and contemporary French society. These sexual minorities of North African origin may explain their homosexuality in terms of a?modern coming out? narrative when living in France. Nevertheless, they are able to negotiate cultural hybridity and flexible language, temporalities, and filiations, that combine elements from a variety of discourses on family, honor, face-saving, the symbolic order of gender differences, gender equality, as well as the western and largely neoliberal constructs of individualism and sexual autonomy.